2005
DOI: 10.1073/pnas.0405318102
|View full text |Cite
|
Sign up to set email alerts
|

Directing oncogenic fusion genes into stem cells via an SCL enhancer

Abstract: TEL-TRKC is a fusion gene generated by chromosomal translocation and encodes an activated tyrosine kinase. Uniquely, it is found in both solid tumors and leukemia. However, a single exon difference (in TEL) in TEL-TRKC fusions is associated with the two sets of cancer phenotypes. We expressed the two TEL-TRKC variants in vivo by using the 3 regulatory element of SCL that is selectively active in a subset of mesodermal cell lineages, including endothelial and hematopoietic stem cells and progenitors. The leukem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Using reporter genes, we have shown that the +19 enhancer directs expression to HSCs in transgenic mice. The Tal1 enhancer has also been used to generate mouse models for inducible transgene expression, retroviral gene transfer, and Cre-mediated recombination as well as the development of acute myeloid leukemia mouse models (Murphy et al 2003;Eguchi et al 2005;Gothert et al 2005;Koschmieder et al 2005). At the molecular level, activity of the +19 element critically depends on binding sites for the Ets and GATA families of transcription factors and this combination of transcription factors constitutes a regulatory code employed by several other enhancers Pimanda et al 2006Pimanda et al , 2007aChan et al 2007;Landry et al 2008) that display similar expression patterns in transgenic assays.…”
Section: Discussionmentioning
confidence: 99%
“…Using reporter genes, we have shown that the +19 enhancer directs expression to HSCs in transgenic mice. The Tal1 enhancer has also been used to generate mouse models for inducible transgene expression, retroviral gene transfer, and Cre-mediated recombination as well as the development of acute myeloid leukemia mouse models (Murphy et al 2003;Eguchi et al 2005;Gothert et al 2005;Koschmieder et al 2005). At the molecular level, activity of the +19 element critically depends on binding sites for the Ets and GATA families of transcription factors and this combination of transcription factors constitutes a regulatory code employed by several other enhancers Pimanda et al 2006Pimanda et al , 2007aChan et al 2007;Landry et al 2008) that display similar expression patterns in transgenic assays.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, cell type-specific activity of this cassette outside the hematopoietic system has not been investigated [58]. The small size and robust in vivo activity of the SCL +18/19 enhancer has led several groups to use it as a way of targeting expression to HSCs [19][20][21][22][23]59]. Therefore, comprehensive analysis of the in vivo activity of the SCL +18/19 enhancer within and outside the hematopoietic system not only provides further insights into transcriptional regulation of SCL but will be vital to interpret current and future mouse models generated using this powerful regulatory element.…”
Section: Discussionmentioning
confidence: 99%
“…The +18/19 enhancer was originally characterized as a 5,245-bp fragment. This fragment has been used to direct HSC expression of several proteins, including SCL itself [19], Cre recombinase [20], tetracycline transactivator [21], the TVA avian retroviral receptor protein [22], and oncogenic fusion proteins [23]. Interpretation of these and future studies using this experimental approach will require detailed knowledge of the precise cell types targeted.…”
Section: Introductionmentioning
confidence: 99%
“…Consistently, a transient enhanced replating ability was observed in MLL(n) and Mll PTD/WT splenocytes ( Figure 1L). Compared to non-transgenic controls, MLL (10)(11)(12)(13)(14)(15) and MLL(80-100) splenocytes, the latter in particular, were able to form a substantial number of secondary colonies ( Figure 1L). Mll PTD/WT splenocytes were able to generate compact myeloid colonies even in the third round of replating ( Figure 1L,M).…”
mentioning
confidence: 97%
“…MLL amplification perturbs myeloid development in mouse models. Total cell counts in (A) bone marrow (2 femurs), (B) thymus and (C) spleen of the control MLL(0), MLL (10)(11)(12)(13)(14)(15), and Mll PTD/WT mice. (D) Total colony numbers generated from bone marrow cells of MLL(n) and Mll PTD/WT mice.…”
mentioning
confidence: 99%